A dificuldade ao se tomar uma decisão sobre internar ou não um familiar em fase terminal sem autonomia - Melo, Luis Augusto de (2006)
This study tries to think about the decisions made by the family when having one of its elder members ill without autonomy. lt is about the therapeutic actions and about the professional acting. Thus, its general purpose was to comprehend how the family decides to hospitalize the patient in terminal stage and without autonomy. A research was performed under the qualitative approach with ethnographic interview used to data collecting. The investigation was developed with health professionals and 8 relatives that rescued by an oral life history, their experiences while taking care of iii elders and dependents. The group was made of six women and two men with ages between 46 and 85 years old, in which the majority had a coliege degree. By the testimoniais of the interviewed ones it was possible to realize the recognizing of new family schemes and their implications to the support they offer its members. Referring to the quality of aging it was possible to observe that the way of living differentiate the healthy aging and the iii one. lt was realized that the process hat involves this reality happens in different ways according to values, to conditions and to the characteristics that constitute the paris of each family. lt became evident that there is an affective behavior and obligation and attached cluties to the commitment of taking care of elders that are III and have no autonomy. lt was realized the importance of health services that need to fulfill their purposes and promote ways and social resources so that the families welcome the ilI elder and are able to provide him/her a support web, assuring his/her continuity in the family nucleus and in the proper community